PERAN IBU DALAM PEMENUHAN KEBUTUHAN NUTRISI PADA ANAK PICKY EATER - HARDJITO, KOEKOEH (HEALTHY : Jurnal Inovasi Riset Ilmu Kesehatan, 2024)
Picky eaters, selective in their food choices, pose a challenge for parents particularly mothers in meeting nutritional needs. This study explores the role of mothers in meeting the nutritional needs of picky eater children. Utilizing a descriptive approach, data was gathered from 30 mothers through interviews and questionnaires.. The results indicate that mothers play a crucial role, including being providers of healthy food, models of healthy eating behavior, nutrition educators, mealtime managers, and creators of a positive eating environment. A total of 60% of mothers have a good role as providers of healthy food and as mealtime managers, while 46.70% of mothers have a sufficient role as nutrition educators. Furthermore, 40% of mothers have a satisfactory role in creating a positive eating environment, and 53.40% of mothers have a less substantial role in the category of modeling healthy eating behavior. While most mothers have good roles, there is a deficiency in the role of being a model of healthy eating behavior. An intensive approach is needed to enhance mothers' understanding and involvement in setting an example of healthy eating behavior for their children. The mother's role is highly significant in addressing the nutritional challenges of picky eater children. The mother's role is not the only factor influencing the success of dealing with picky eaters; the support and participation of other family members are also significant. A holistic approach involving the entire family is required for optimal results. ABSTRAKAnak picky eater, merupakan anak yang selektif dalam memilih makanan, menjadi tantangan tersendiri bagi orang tua khususnya ibu dalam memenuhi kebutuhan nutrisi. Penelitian ini mengeksplorasi peran ibu dalam memenuhi kebutuhan nutrisi anak picky eater.. Dengan menggunakan pendekatan deskriptif, data dikumpulkan dari 30 ibu melalui wawancara dan pengisian kuesioner. Hasil menunjukkan bahwa ibu memiliki peran krusial, termasuk sebagai penyedia makanan sehat, model perilaku makan sehat, edukator nutrisi, pengelola waktu makan, dan pencipta lingkungan makan positif. Sebanyak 60% ibu memiliki peran dalam kategori baik sebagai penyedia makanan sehat dan sebagai pengelola waktu makan, sebesar 46.70% ibu memiliki peran cukup sebagai edukator nutrisi. Selanjutnya  40% ibu memiliki peran cukup dalam menciptakan lingkungan makan yang positif dan terdapat 53.40% ibu memiliki peran dalam kategori kurang sebagai model perilaku makan sehat. Walaupun sebagian besar ibu memiliki peran baik, terdapat kekurangan pada peran sebagai model perilaku makan sehat. Diperlukan pendekatan intensif untuk meningkatkan pemahaman dan keterlibatan ibu dalam memberikan contoh perilaku makan sehat kepada anak-anak. Peran ibu sangat penting dalam mengatasi tantangan pemenuhan kebutuhan nutrisi anak picky eater. Peran ibu bukan satu-satunya faktor yang memengaruhi keberhasilan mengatasi anak picky eater, melainkan juga dukungan dan partisipasi anggota keluarga lainnya. Pendekatan holistik yang melibatkan seluruh keluarga diperlukan untuk hasil optimal.